2015
DOI: 10.3389/fnsys.2015.00130
|View full text |Cite
|
Sign up to set email alerts
|

Distinguishing cognitive state with multifractal complexity of hippocampal interspike interval sequences

Abstract: Fractality, represented as self-similar repeating patterns, is ubiquitous in nature and the brain. Dynamic patterns of hippocampal spike trains are known to exhibit multifractal properties during working memory processing; however, it is unclear whether the multifractal properties inherent to hippocampal spike trains reflect active cognitive processing. To examine this possibility, hippocampal neuronal ensembles were recorded from rats before, during and after a spatial working memory task following administra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 62 publications
0
11
0
Order By: Relevance
“…All data was previously used in a study on the effects of cannabinoids on hippocampal multifractality [21, 22]. Briefly, in the sample phase, the rats were presented one of two levers.…”
Section: Resultsmentioning
confidence: 99%
“…All data was previously used in a study on the effects of cannabinoids on hippocampal multifractality [21, 22]. Briefly, in the sample phase, the rats were presented one of two levers.…”
Section: Resultsmentioning
confidence: 99%
“…To the authors' best knowledge, this is the first time that MFDFA has been used for discrimination of ADHD. Several recent studies suggest that changes in the multifractal structure of EEG signal reflect changes in the adaptability of underlying physiological process [19,21]. According to the results shown in Fig.…”
Section: Discussionmentioning
confidence: 91%
“…Fractal analysis of EEG time series has proved to be useful for describing brain activity during sleep [20]. Fetterhoff et al [21] show that multifractal firing patterns of hippocampal spike trains are more complex during a working memory task and significantly declined with the administration of memory impairment in rats. Zorick et al [19] showed the capability of MFDFA to interfere with the recognition of changes in states of consciousness.…”
Section: Introductionmentioning
confidence: 99%
“…EEG signals were filtered with a 16th order Butterworth band-pass filter to extract four typical frequency bands: delta (0.5-4 Hz), theta (4-8 Hz), alpha (8)(9)(10)(11)(12)(13), and beta (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30). For each band, power was calculated by invoking Perceval's theorem and summing the signal in the time domain [22].…”
Section: Eeg Frequency Band Powermentioning
confidence: 99%